On the Equilibrium and Welfare Consequences of 'Keeping up with the Joneses' - Frédéric Gavrel; Therese Rebiere (Institute for the Study of Labor (IZA), 2015)
This paper provides an analysis of the social consequences of people seeking to keep up with the Joneses. All individuals attempt to reach a higher rank than the Joneses, including the Joneses themselves. This attitude gives rise to an equilibrium in which all individuals have equal utilities but unequal (gross) incomes. Due to a rat-race effect, individuals devote too much energy to climbing the social scale in this equilibrium. However, laissez-faire equilibrium is an equal-utility constrained social optimum. Unexpectedly, numerical simulations show that this theory could account for the observed distribution of intermediate wages.
Keywords: D3; D6; D8; I3; Z1; 330; Keeping up with the Joneses; social interactions; well-being; inequalities; efficiency